THE EFFECTIVENESS OF READING, MIND MAPPING, AND SHARING (RMS) IN TRIGONOMETRY - S, Nadiyah Amanati; Hamdani, Hamdani; Siregar, Nurfadilah; Halini, Halini; Mirza, Ade (Journal of Authentic Research on Mathematics Education (JARME), 2024)
This study aims to describe the effectiveness of the RMS learning model on trigonometry material. The method used is quantitative with a one-shot case study design. The subjects of this research are the tenth-grade students at SMAN 1 Silat Hulu. The research instruments consist of tests and non-tests. The non-test instruments include observation sheets and questionnaires, while the test instrument is in the form of essay questions. The effectiveness of the RMS learning model is evaluated based on three categories: learning outcomes, student responses through questionnaires, and student learning activities observed through observation sheets. The results of the study indicate that the RMS learning model is effective in teaching trigonometry, with student learning mastery reaching 100%, student activity showing more than 100% engagement, and student responses to this learning model being 100% positive. The research discussion highlights that the RMS learning model not only improves learning outcomes but also enhances student engagement and positive responses. The implementation of the RMS learning model is recommended for educators to apply to appropriate materials to improve the quality of learning and student involvement.